Community of learners reflections on the development of creative thinking in music education processes (Revista da Tulha, 2015)
In this work, we intend to discuss the role of creative music making in music education with a view to recognizing actions that may contribute to the integral development of human beings and encourage the acquisition of autonomy. For this, we use data collected from recent national survey, developed by GEPEM - Group of Study and Research in Music Education at UNESP Arts Institute - with support by FAPESP. The work is based on Murray Schafer’s, John Paynter’s and Chefa Alonso’s ideas. We advocate the importance of works that encourage musical thinking, coupled with the experience of the culture in which the group is inserted. The issue of creative thinking development has relevance today, due to the possibilities it brings to Brazilian educational institutions, in this historical moment in which, under federal law, music becomes an obligatory component in basic education. After a lapse of over 40 years and at a time when the world has undergone profound changes, it is necessary to seek alternatives that provide adequate tools to institutions and persons responsible for basic education. To understand music education as a collective activity, community character can be an interesting way, and perhaps the only one, to share the responsibility of teaching and learning among members of the group - a community of learners, which is the title of this work. This reflection comes to proposals that are part of a world view of ecological character, in which competitiveness and intense appreciation of the technicist character of music education give way to mutual respect, to working collectively, the division of responsibilities and integral development human.